Answer:
6
Step-by-step explanation:
5% of 120 were late
=
× 120
= 0.05 × 120
= 6
Answer:
False
Step-by-step explanation:
They don't look alike
Given:
The equation of a circle is
![x^2+y^2=10](https://tex.z-dn.net/?f=x%5E2%2By%5E2%3D10)
A tangent line l to the circle touches the circle at point P(1,3).
To find:
The equation of the line l.
Solution:
Slope formula: If a line passes through two points, then the slope of the line is
![m=\dfrac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%3D%5Cdfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
Endpoints of the radius are O(0,0) and P(1,3). So, the slope of radius is
![m_1=\dfrac{3-0}{1-0}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B3-0%7D%7B1-0%7D)
![m_1=\dfrac{3}{1}](https://tex.z-dn.net/?f=m_1%3D%5Cdfrac%7B3%7D%7B1%7D)
![m=3](https://tex.z-dn.net/?f=m%3D3)
We know that the radius of a circle is always perpendicular to the tangent at the point of tangency.
Product of slopes of two perpendicular lines is always -1.
Let the slope of tangent line l is m. Then, the product of slopes of line l and radius is -1.
![m\times m_1=-1](https://tex.z-dn.net/?f=m%5Ctimes%20m_1%3D-1)
![m\times 3=-1](https://tex.z-dn.net/?f=m%5Ctimes%203%3D-1)
![m=-\dfrac{1}{3}](https://tex.z-dn.net/?f=m%3D-%5Cdfrac%7B1%7D%7B3%7D)
The slope of line l is
and it passs through the point P(1,3). So, the equation of line l is
![y-y_1=m(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3Dm%28x-x_1%29)
![y-3=-\dfrac{1}{3}(x-1)](https://tex.z-dn.net/?f=y-3%3D-%5Cdfrac%7B1%7D%7B3%7D%28x-1%29)
![y-3=-\dfrac{1}{3}(x)+\dfrac{1}{3}](https://tex.z-dn.net/?f=y-3%3D-%5Cdfrac%7B1%7D%7B3%7D%28x%29%2B%5Cdfrac%7B1%7D%7B3%7D)
Adding 3 on both sides, we get
![y=-\dfrac{1}{3}x+\dfrac{1}{3}+3](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B1%7D%7B3%7Dx%2B%5Cdfrac%7B1%7D%7B3%7D%2B3)
![y=-\dfrac{1}{3}x+\dfrac{1+9}{3}](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B1%7D%7B3%7Dx%2B%5Cdfrac%7B1%2B9%7D%7B3%7D)
![y=-\dfrac{1}{3}x+\dfrac{10}{3}](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B1%7D%7B3%7Dx%2B%5Cdfrac%7B10%7D%7B3%7D)
Therefore, the equation of line l is
.
Answer:
95
Step-by-step explanation:
304/3.2 = 95
Answer:
Which expression is equal to
?
The correct answer is B.
![4a^{2}b^{2}c^{3}(\sqrt[3]{b})](https://tex.z-dn.net/?f=4a%5E%7B2%7Db%5E%7B2%7Dc%5E%7B3%7D%28%5Csqrt%5B3%5D%7Bb%7D%29)
Step-by-step explanation:
Inside of the radical you have
. If you find the cube root of that, you get 4a^2. Go ahead and write that outside of the parenthesis:
![4a^{2}](https://tex.z-dn.net/?f=4a%5E%7B2%7D)
![\sqrt[x}](https://tex.z-dn.net/?f=%5Csqrt%5Bx%7D)
![\sqrt[3]({b^{7}c^{9}})](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%28%7Bb%5E%7B7%7Dc%5E%7B9%7D%7D%29)
If you re-write what is inside of the radical, you get:
![4a^{2}(\sqrt[3]{b^{3}*b^{3}*b^{1}*c^{3}*c^{3}*c^{3} }](https://tex.z-dn.net/?f=4a%5E%7B2%7D%28%5Csqrt%5B3%5D%7Bb%5E%7B3%7D%2Ab%5E%7B3%7D%2Ab%5E%7B1%7D%2Ac%5E%7B3%7D%2Ac%5E%7B3%7D%2Ac%5E%7B3%7D%20%20%20%7D)
Basically I expanded what was inside of the radical so I could find the cube roots of b^7 and c^9.
Now, take the cube root of b^7:
![4a^{2}b^{2} (\sqrt[3]b*c^{3}*c^{3}*c^{3} })](https://tex.z-dn.net/?f=4a%5E%7B2%7Db%5E%7B2%7D%20%28%5Csqrt%5B3%5Db%2Ac%5E%7B3%7D%2Ac%5E%7B3%7D%2Ac%5E%7B3%7D%20%20%20%7D%29)
Notice how I could only factor out the two "b^3" that were inside the radical symbol, and how I left the b^1 inside the radical symbol because I couldn't factor it out.
Let's now get the cube root of c^9. Since it's a perfect cube, there won't be any "c"s left inside of the radical symbol:
![4a^{2}b^{2}c^{9}(\sqrt[3]b)](https://tex.z-dn.net/?f=4a%5E%7B2%7Db%5E%7B2%7Dc%5E%7B9%7D%28%5Csqrt%5B3%5Db%29)